A Risk Management Framework for Scrum Projects - Lopes, Samuel de Souza; Souza, Rogeria Cristiane Gratao de [UNESP]; Contessoto, Allan de Godoi [UNESP]; Oliveira, Andre Luiz de; Braga, Rosana Teresinha Vaccare; Filipe, J.; Smialek, M.; Brodsky, A.; Hammoudi, S. (Scitepress, 2021)
Software changes constantly to suit the market volatility, causing risks to the project. Agile software development approaches, such as Scrum, have been proposed to deal with constant changes in project requirements. In Scrum, the Product Owner (PO) is responsible for managing such changes and ensuring that the developed software brings significant value to the customers. However, there are potential risks involved in these responsibilities. If not properly managed, they can lead to project failure. In this paper, we introduce a novel approach to managing risks involving PO's roles. In our work, we tailored the risk management knowledge area from the Project Management Body of Knowledge Guide into the Scrum. We established a framework called RIsk Management PRoduct Owner (RIMPRO), which intends to support project teams to systematically manage risks related to PO activities that may arise during the project. As proof of concept, the processes described in RIMPRO were evaluated by potential users. Through a preliminary assessment, we observed that RIMPRO is promising since it can assist teams in managing risks involving PO in a systematized and effective manner.
Keywords: Agile Software Development; Scrum; Product Owner; Project Management; Risk Management